2013
DOI: 10.4067/s0716-97602013000200010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dangguibuxue Tang, a Chinese herbal medicine, on growth performance and immune responses in broiler chicks

Abstract: The eff ects of Dangguibuxue Tang (DBT) on growth performance and immunity response in immunosuppressed broiler chicks were investigated in this study. 240 one-d-old broiler chicks (DaHeng S01) were randomly divided into 4 groups, 2.0% DBT-treatment (A), 0.5% DBT-treatment (B), cyclophosphamide-control (C), and control group (D). From 4 d to 7 d of age, chicks in group A, B and C were given cyclophosphamide (CY) at a dosage of 100mg/kg body weight (BW) daily by intraperitoneal injection to induce immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Traditional Chinese medicine has been acknowledged as a major source of medicine, which was used for centuries around the world [ 10 , 11 ]. Dangguibuxue decoction (DBD), a Chinese medicinal decoction that contains Angelicae sinensis radix (Danggui) and Astragalus radix (Huangqi) at a ratio of 1:5, has been widely used to treat blood deficiency disease in China for more than 800 years because of the hematopoietic properties of this prescription [ 12 ]. In Chinese, the herb Angelica sinensis is pronounced as Dang Gui; Bu Xue refers to hematopoietic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine has been acknowledged as a major source of medicine, which was used for centuries around the world [ 10 , 11 ]. Dangguibuxue decoction (DBD), a Chinese medicinal decoction that contains Angelicae sinensis radix (Danggui) and Astragalus radix (Huangqi) at a ratio of 1:5, has been widely used to treat blood deficiency disease in China for more than 800 years because of the hematopoietic properties of this prescription [ 12 ]. In Chinese, the herb Angelica sinensis is pronounced as Dang Gui; Bu Xue refers to hematopoietic effects.…”
Section: Introductionmentioning
confidence: 99%
“…DBT has been reported to promote erythropoietin, platelets, and angiogenesis [ 23 ]. The effects of stimulating the immune response [ 24 ] and alleviating myocardial damage [ 25 ] have also been reported [ 24 ]. DBT is composed of Angelica and Astragalus , and both herbs showed possible improvement in ovarian function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed numerous beneficial effects of DBT, such as renoprotective [ 40 ], hepatoprotective [ 41 , 42 ], cardioprotective [ 43 ], pulmonary protective [ 44 , 45 ], anti-inflammatory [ 46 ], immunostimulant [ 47 , 48 ], antioxidant [ 49 , 50 ], and erythropoietic [ 51 , 52 ] properties. However, the majority of these studies were in vitro tests and used animal models.…”
Section: Discussionmentioning
confidence: 99%